How Functional Team Roles Mitigate the Effect of Conflict on Team Performance - Mumford, Troy (Advances in Social Sciences Research Journal, 2020)
Work team structures are used in organizations to achieve higher performance, enable greater creativity, and create more political buy in. The literature suggests that when teams are able to coherently carry out certain functional team roles, conflict is better managed and higher performance is achieved. This study investigates these claims in a sample of 449 individuals working in 94 project teams over two project types. Findings indicate that the performance of task and social team roles was negatively related to task and relationship conflict for both work types. In addition, Spanning roles were negatively associated with conflict only for the more complex project. Finally, functional team roles were associated with team performance for both project types. The implications for researching and managing roles in work teams are discussed.